Comprehensive Understanding of Fatigue, Breakdown, and Recovery Mechanism by Thickness Scaling in Hf0.5Zr0.5O2/Ge MF(I)S Capacitors for Low Writing Voltages - Jeong, Jai-Youn; Ko, Kyeol; Shin, Changhwan; Han, Jae-Hoon (AMER CHEMICAL SOC, 2025)
The main challenges in HZO-based ferroelectric capacitors (FeCAPs) and ferroelectric field-effect transistors (FeFETs) are the comparatively high coercive voltage and thicker HfxZr1-xO2 (HZO) thickness, limiting their application in embedded nonvolatile ferroelectric memory. Therefore, there is a critical need to enhance endurance cycles (>10(5)) while achieving relatively larger 2P(r) and faster switching speeds under low operating voltages (<2 V) in thin HZO film ferroelectric capacitors. While some fundamental studies have addressed these challenges using metal-ferroelectric-metal (MFM) capacitors, there is a lack of mechanism analysis and methods to recover polarization switching about fatigue-limited endurance (typically <10(5) at low electric fields) in thin HZO films in the case of metal-ferroelectric-(insulator)-semiconductor (MF(I)S) structures. In this study, we conducted a detailed investigation into the effect of thickness scaling of HZO on germanium MF(I)S capacitors. We achieved a low coercive voltage under 1.65 V through HZO thickness scaling for low-voltage operation. To evaluate its endurance characteristics, we elucidated the relationship between reversible polarization and polarization switching, an important electrical analysis approach for understanding the fatigue state. Furthermore, we comprehensively investigated that endurance cycles can be restored by applying optimal wake-up electric field cycling after entering the fatigue state. The thinner HZO capacitor at 500 degrees C exhibited superior ferroelectric properties, including large polarization, low switching voltage, low leakage, improved breakdown field, endurance recovery, and over 10 years of data retention. The increase in reversible polarization transition and internal electric field related to charge trapping during low-voltage operating cycles can be comprehended by carefully examining the polarization recovery mechanism under fatigue and rewake-up conditions. Through these discussions, we provide insights into the polarization mechanism of HZO/Ge MF(I)S and the basic strategy for achieving superior ferroelectric memory.